Peran self-esteem terhadap hopelessness dalam pencarian kerja pada lulusan baru generasi z di Yogyakarta - Ulandari, Farastia; Triyantoro, Davit Bagus (Jurnal Psikologi Poseidon, 2026)
Hopelessness is a feeling of despair or loss of hope for the future in finding employment. One way to overcome hopelessness is by improving self-esteem. This study aims to determine the relationship between self-esteem and hopelessness in job-seeking among generation Z fresh graduates in Yogyakarta City. This study employs a quantitative correlational approach using purposive sampling, involving 201 recent Gen Z graduates in Yogyakarta aged 20–29 who are currently unemployed. The research instruments used the Self-Esteem Scale and the Hopelessness Scale administered Google Form. The results of the hypothesis test using Pearson’s product-moment correlation test indicate a highly significant negative relationship between self-esteem and hopelessness among Generation Z recent graduates in Yogyakarta, thus the research hypothesis is accepted. This implies that strengthening positive self-esteem can serve as a strategy for recent graduates to reduce feelings of hopelessness during the job search process.